User scheduling based on angles with block diagonalization in MU‐MIMO broadcast. (6th March 2017) - Yuan, Kun; Cao, Yewen; Zhang, Huanjing
Summary: This paper investigates user selection scheme in the multiuser multiple‐input multiple‐output (MU‐MIMO) broadcast (BC) scene with block diagonalization precoding. Block diagonalization is a suboptimal but practical linear precoding method, which can eliminate the multiuser interference by turning the MU‐MIMO BC channel into parallel MIMO channels. With this precoding method, we propose the best user from the user subset to maximize the total throughput in the MU‐MIMO BC system. The angles between subspaces used in this paper are induced from n ‐inner product, an extension from norm space to the n ‐dimensional space, which characterizes the orthogonality between subspaces. One of the algorithms achieves good performance by comparing the capacity greedily, the other one attains high capacity by reducing the cardinality of the user subset to improve the orthogonality between the user channels, which could be seen as a complexity reduction algorithm with respect to the former one. Indeed, they are all based on the angles between subspaces. Analysis shows that both of the proposed algorithms have lower complexity and better performance than the classical algorithms. The numerical results also confirm our analysis. Abstract : This paper focuses on finding some user scheduling algorithms with a good trade‐off between the computation complexity and system capacity in BD MU‐MIMO downlink system. On the basis of maintaining high system capacity, we propose two low complexity algorithm derived from n ‐norm‐based spatial angle. Both the complexity analysis and simulation results demonstrate that the proposed GUSBA and USBS methods achieve low computation complexity and high system capacity over the conventional BD‐n Alg., and also make a good trade‐off between the complexity and system capacity.